2011
DOI: 10.1097/wad.0b013e31820d89b6
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Profiles in Dementia

Abstract: We compared patterns of neuropsychiatric symptom across four dementia types (AD, VAD, DLB, PDD), and two mixed groups (AD/VAD, AD/DLB) in sample of 2,963 individuals from the National Alzheimer's Coordinating Center Uniform Data Set between September 2005 and June 2008. We used confirmatory factor analysis to compare neuropsychiatric symptom severity ratings made by collateral sources on the Neuropsychiatric Inventory (NPI-Q) for people with Clinical Dementia Rating scores of 1 or higher. A three factor model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…bvFTD has a broad differential diagnosis of both neurodegenerative and psychiatric disorders, resulting in a similar late-onset behavioral syndrome [4,5,6,7,8,9,10,11,12,13]. Although biomarkers take a prominent position in the present FTDC criteria, it is still unclear how they can distinguish between bvFTD and a representative control group [3].…”
Section: Introductionmentioning
confidence: 99%
“…bvFTD has a broad differential diagnosis of both neurodegenerative and psychiatric disorders, resulting in a similar late-onset behavioral syndrome [4,5,6,7,8,9,10,11,12,13]. Although biomarkers take a prominent position in the present FTDC criteria, it is still unclear how they can distinguish between bvFTD and a representative control group [3].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ostling and colleagues, 33 who evaluated 85-year-old patients with dementia, found that 53.6% of individuals with vascular dementia had psychotic symptoms (26.1% had hallucinations, and 42% had delusions), whereas another study found that 14% of patients had hallucinations, and 27% had delusions. 34 In vascular dementia, as in Parkinson's dementia, but not Alzheimer's or Lewy body dementia, the severity of dementia does not appear to be associated with the presence or severity of psychosis. 33,34 Secondary Psychoses In addition to the aforementioned neuropsychiatric disorders, a variety of medical and neurological problems in older individuals can result in psychosis.…”
Section: Alzheimer's Disease and Other Dementiasmentioning
confidence: 97%
“…17 As in Alzheimer's disease, increased dementia severity is associated with increased psychosis severity. 34 As in Parkinson's disease, visual hallucinations are often well formed and nonfrightening in Lewy body dementia, but clinically the two are distinguished by the temporal relation between dementia onset and the onset of parkinsonian features; in Lewy body dementia the onset of dementia symptoms typically occurs soon (within one year) after the onset of parkinsonism. 18 As with the aforementioned dementias, psychotic symptoms are common in vascular dementia, and presumably, the likelihood of psychosis depends on the severity and extent of infarction.…”
Section: Alzheimer's Disease and Other Dementiasmentioning
confidence: 98%
See 2 more Smart Citations